Investigating Of Effective Parameters On Stress Behavior Of Pressure Deep Twin Tunnels Under Pressure - Panji, Mehdi; Kavandi, Pouya (The Turkish Online Journal of Design Art and Communication, 2016)
The twin tunnels under the pressure have been analyzed in this study. Full-plane boundary element method (BEM) has been used for modeling. Focus of meshing on the boundary of twin tunnels distinguishes distinct features of the mentioned method with other numerical methods. In this regard, in addition to providing generalities of elastostatic formulation of the method and the required verification, the numerical study of the two tunnel has been done on stress and displacement components. The results showed that if the distance between two tunnel was more than 30R (R radius of tunnel), the vertical stress on the wall of one of the twin tunnels was converged towards an alone tunnel.
Keywords: BEM; deep twin tunnels; stress behaviors; effective radius